âTHE GANERSâ KAPAL PEMBERSIH SAMPAH DENGAN SISTEM LAMBUNG TIGA SEBAGAI SOLUSI PEMBERSIH SAMPAH DI TELUK JAKARTA - Basir, Idham Aulia Muhammad; Pratiwi, Titis Wahyu; Saputra, Sabella Nisa; Kamesworo, Windy; A., Ardiansyah (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Jakarta bay is a bay in Laut Jawa located in north of DKI Jakarta province. Jakarta bay is one of dirtiest place in the world. To overcome that problem, this study designed âThe Ganers (The Garbage Cleaner Ship)â. There is innovation technology of water garbage cleaner which is effective, innovative, and applicative in effort to increase marine potency in Jakarta bay. The Ganers take principle of Trimaran ship (three sides ship) that equipped by many specification of machine. Tools which is will be paired to that ship used to facilitate to run process cleaning the water garbage.